Factors Contributing to poor Academic Performance in Kenya Certificate of Secondary Education in Public Secondary Schools in Kericho County, Kenya. - Onderi, Henry; Kiplangat, Rono Kenneth; Awino, James (Kenya Journal Of Educational Planning Economics and Management, 2019)
Performance of students is a product of socio-economic,psychological and environmental factors.Education plays a significant role in societal transformation and development.And progression to university or further training depends on the achievements at Kenya Certificate of Secondary Education in form four.This study aimed at finding out factors that contribute to poor performance in Kenya Certificate of Secondary Education in public secondary schools in Kericho sub-county,Kericho county, Kenya. The study was done by developing a conceptual framework in relation to factors contributing to poor academic performance in secondary schools . Selected literature revealed that the major highlights on causes of poor academic performance are; student-based factors, parent-based factors, teacher-based factors and school-based factors, family background, socio-economic status and school factors. However, there is need to find out what other factors are causing poor academic performances among students and the extent of these causes. A descriptive survey design was used. Data was collected from 21 secondary schools and a sample of 16 headteachers,64 teachers,128 form four students and 32 parents was used. In total, the study had 240 respondents. Data was analyzed using SPSS with use of frequencies and percentages. It was discovered that the following factors contributed to poor performance in secondary schools national examinations ; Students being slow to learn , students are solely responsible , students’ motivation in class , the level of income of parents , parents are responsible , parents upbringing , parents level of literacy and parental education ,parents need to participate in encouraging the student to perform better , teachers’ attitude towards students, teachers motivation , teachers’ attitude to their jobs , teachers allowing students to consult, teaching methods , the level of education of teachers , family background , family structure , peer influence , classroom management , learning environment in terms of space and conduciveness and finally leadership styles. The study found out that majority of respondents agreed that these factors are key to a students’ poor performance amongst other factors especially social economic. The study recommended that there is a strong need for sensitization, Students should approach their teachers for help , schools should offer career guidance to students and have extra time for the students , parents should encourage students , The government should improve on free education policies and provision of more funds and materials for the upliftment of the educational system . The study suggested areas of further research on social economic factors and sources of factors contributing to poor academic performance as raised by the respondents .The study was expected to give insight reference to policy makers, scholars and researchers in order to improve the weak areas